ANALISIS PERBANDINGAN MANAJEMEN OPERASIONAL PADA PEGATRON CORPORATION SEBELUM, SELAMA, DAN SETELAH PANDEMI - Cuandra, Fendy; Lysion, Olivia; Wijaya, Charlie; Andyana; Gunadi, Jacky (Transpublika Publisher, 2023)
This study analyzes the operational management of Pegatron Corporation, a Taiwan-based manufacturing company that expanded to Batam, Indonesia in July 2019. Pegatron Corporation produces a variety of computing devices such as notebook and desktop PCs and motherboards, as well as consumer electronics like tablets, game consoles, and multimedia players. In addition, the company also manufactures communication devices including smartphones, broadband and networking devices. The research objective is to compare Pegatron Corporation's operational management before, during, and after the Covid-19 pandemic using a qualitative approach in the city of Batam. The study focuses on key areas such as manufacturing processes, materials management, and supply chain management.